Bacterial Indoor-Air Load and its Implications for Healthcare-Acquired Infections in a Teaching Hospital in Ethiopia - Shiferaw, Teklu; Gebr-silasse, Lakew; Mulisa, Girma; Zewidu, Adinew; Belachew, Feleke; Muleta, Daba; Zemene, Endalew (International Journal of Infection Control, 2016)
Lack of regular cleaning and disinfection practices of the hospital environment is among the main factors for the spread of healthcare-acquired infections(HAIs). The aim of this study is to determine bacterial indoor air load and antimicrobial susceptibility pattern of isolates from rooms of Adama Hospital Medical College in Ethiopia. A cross-sectional study was conducted from May to August 2013. A total of 78 indoor air samples were collected from 29 medically sensitive rooms of the hospital. Using passive air sampling method, a 90mm diameter Petri plate containing Sheep Blood agar(Oxoid, UK) was left open according to the 1/1/1 scheme. The samples were processed following standard bacteriological procedures at diagnostic bacteriology unit, Oromia Public Health Laboratory(OPHRCBQAL). Data were analyzed using SPSS version 16.0. Overall, 182 bacterial isolates were recovered with an average of 3.42 bacterial species/room. The predominant isolates were coagulase negative Staphylococci(CNS)(42.9%), followed by S. aureus(20.3%). Pseudomonas spp.(10.4%), E. coli(6.6%) and Salmonella spp.(6%). Bacterial indoor air load in all the hospital rooms included in the study was higher than the acceptable standard. The highest mean colony forming units was obtained in Obstetrics and surgical wards. Eight percent of the S. aureus and 7.6% of the CNS were resistant to 8 and 7 classes of antibiotics including Methicillin, respectively. The indoor air bacterial load of the hospital rooms was beyond the acceptable standard. Profile of the isolates revealed the presence of multidrug resistant causative agents of HAI. Hence, safety precautions should be strictly followed in the hospital to prevent tragic outcomes of HAIs.